PENERAPAN GOVERNANCE DALAM IMPLEMENTASI PERDA PENYANDANG DISABILITAS DI KOTA DENPASAR (Studi Kasus Implementasi Peraturan Daerah Provinsi Bali Nomor 9 Tahun 2015 Tentang Perlindungan Dan Pemenuhan Hak Penyandang Disabilitas) - Octaviani, Ni Putu Evilia; Erviantono, Tedi; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2016)
ABSTRACT In the area of Bali, regulation that related to persons with disabilities is a new thing created by the executive and legislature, then ratified in 2015. The passing of a regulation can not be separated from the implementation of the regulation because the success of regulation is determined by the implementation being done to realize these policies. Given that implementation becomes very important, therefore it will be very important as well for each element associated with regulation to implement the regulation together that provide benefits for persons with disabilities. In this study, the authors use descriptive qualitative research method, which make the process of data collection by observation and interview techniques as well as linking with the existing theory. The theory used is the theory of governance by focusing on the concept of participation, justice, and implementation. The theory and the concept would be attributed to Regulation No. 9 of 2015 on the Protection and Fulfillment of the Rights of Persons with Disabilities, which assessed the participation of the various elements of government, private and community, considering the issues related to persons with disabilities is a cross cutting issue that not only addressed by one side but the various side concerned. So it is with justice that earned by persons with disabilities by the existence of regulation. It will demonstrate the implementation of disabilities Regulation by applying the principles of governance. Keywords: governance, implementation, Regulation No. 9 of 2015, persons with disabilities